Toward high production of graphene flakes – a review on recent developments in their synthesis methods and scalability. Issue 31 (25th July 2018) - Kairi, Muhammad Izhar; Dayou, Sebastian; Kairi, Nurul Izni; Bakar, Suriani Abu; Vigolo, Brigitte; Mohamed, Abdul Rahman
Abstract : Graphene flakes, one of the most popular form of graphene, can be used for many applications. Their synthesis is in the path to reach the large-scale production if the cost of production is further improved. Abstract : Research and development in graphene synthesis has been rapidly growing in the past few years because of its extraordinary physical, mechanical, thermal, electrical and optical properties. Graphene flakes, one of the most popular forms of graphene, can be used for many applications such as conductive inks, nanofluids, supercapacitors, composites, etc. Synthesis of graphene flakes is indeed a path to reach large-scale production even if the cost of production and efficiency are required to be further improved. This review sheds light on the recent advancements of graphene flake synthesis and it gives a comprehensive analysis of the synthesis methods. Keys for further improvements are proposed based on the mechanisms involved in the graphene flake formation.